Pengembangan Motif Daun Pare Sebagai Motif Hias Karya Pintu Kuwadi Di Galih Ukir - I Putu Maha Diadnyana; I Nyoman Dana; Ni Kadek Karuni (Hastagina : Jurnal Kriya Seni, 2022)
This creation was made with the aim of developing one of the decorative styles in Galih Ukir with the title: "Development of Galih Ukir Pare Leaf Motifs as Ornaments for the Embodiment of Kuwadi Doors". From the explanation of this title, a design development will be carried out, especially from the Pare decorative motif found in Galih Ukir so that we look forward to a new motif from the results of this development which will be applied to the kuwadi door product. In addition to the development of the ornamental pare leaf motif in Galih Ukir, the problems that must be solved are the production process of the kuwadi door during the internship/work practice, the form of development of the bitter melon leaf motif, and the finishing techniques applied to the kuwadi door work. In creation using the methodology, it is generally described in terms of exploratory, experimental, and driven by real issues identified in the practice of the work and reinforced by the theory of the three pillars of craft creation formulated by SP Gustami such as exploration, planning, and embodiment. In the discussion it can be concluded that the implementation of the creation of a kuwadi door with the motif of developing bitter melon leaves with the production process or the realization of a kuwadi door is carried out through various stages starting from the design stage, the material processing process, to the final stage, namely the finishing stage, so that a kuwadi door with a development motif is realized. bitter melon leaves in Galih Ukir. And during the implementation of the internship, the knowledge gained is related to knowledge, skills and technology in the realization or production process of kuwadi doors with ornamental motifs of developing bitter melon leaves.